(untitled) (Pedagogy of Higher and Secondary Education, 2009)
The article is dedicated to the subject , structure and levels of the professionalism of modern teacher’s activity concerning the organization of the country studies work with pupils from the viewpoint of theory of pedagogical acmeology and pedagogical management. Certain attention is paid to the aspects concerning the preparing of the teacher to the activities of this kind.